PENGARUH SERVICE RECOVERY TERHADAP KEPUASAN KONSUMEN UNTUK MENINGKATKAN MINAT GUNA JASA ULANG - Wicaksono, Bagas; Magnadi, Rizal Hari (Diponegoro Journal of Management, 2015)
The development of Indonesia aitlines grow rapidly. With low-cost base airline, there are still a lot of people who want to use airlines. Lion Air as low-cost airline market leader, still encounter a service failure such as delay. This study aims to analyzes the service recovery for service failure.            This study analyzes the dimension of service recovery. Distributive justice, procedural justice, and interactional justice the effect to consumen satisfication and repurchase intention. The study was conducted on 120 respondents who qualified to provide for the completed questionnaires.            The result of this study show that all of independent dimensions have positive effect on dependent dimensions. Distributive justice have the strongest effect on consumen satisfaction and repurchase intention. The other variable have positive effect but not significant.